WWOX maintains epidermal identity and suppresses EMT to prevent aggressive cutaneous squamous cell carcinoma - Tirza Bidany-Mizrahi; Kian Maroun; Mara Mancini; Osama Hidmi; Ihab Ansari; Jonathan Monin; Tal Keidar Haran; Alexander Maly; Gerry Melino; Eleonora Candi; Rami I. Aqeilan (Proceedings of the National Academy of Sciences, 2026)
Cutaneous squamous cell carcinoma (cSCC), the second most common skin cancer, remains a major health burden worldwide. The WW domain–containing oxidoreductase (WWOX) is frequently altered in cancer; however, its role in epidermal biology and skin carcinogenesis remains undefined. Here, we uncover an essential function for WWOX in safeguarding epithelial identity and restraining cSCC progression. Using conditional knockout mice, we demonstrate that WWOX loss accelerates p53-driven cSCC, resulting in early, highly penetrant, and poorly differentiated tumors. Transcriptomic profiling revealed that WWOX deficiency drives epithelial-to-mesenchymal transition (EMT) and transcriptional plasticity, hallmarks of aggressive disease. Mechanistically, proximity ligation assays together with biochemical and cellular analyses support a close association between WWOX and p63 and imply that WWOX contributes to p63 stabilization; loss of WWOX reduces p63 protein levels and diminishes its binding to epithelial target genes, thereby disrupting epidermal transcriptional programs. Human tissue microarrays confirmed a concordant reduction of WWOX and p63 in advanced cSCC, correlating with poor differentiation. Functional assays in human keratinocytes and cSCC cells further showed that WWOX depletion enhances EMT plasticity, invasiveness, and metastatic colonization. Together, these findings identify WWOX as a critical regulator of epidermal integrity and reveal a previously unrecognized WWOX–p63 axis that constrains EMT and tumor progression in cSCC.